Educational Administration System in Improving the Quality of Education - Sakirman, Sakirman; Andrinata, Andrinata (Tinta Emas Institute, 2024)
In the implementation of Education that takes place in schools, teachers play a very significant role. In this case, it describes the results of research in one of the educational institutions at Madrasah Aliyah Yaqin Pemondah, the importance of the educational administration system to be implemented as one of the benchmarks for the quality of education, especially in the teaching and learning process, but in its implementation it is still not optimal. This study aims to answer the problem of the educational administration system in improving the quality of education by using descriptive qualitative research. The results of this study indicate that it is necessary to organize the educational administration system to improve the quality of education, including (1) management of the teaching and learning process, (2) evaluation plans (3) curriculum management, (4) management of personnel, (5) management of facilities (6) financial management, (7) student services, (8) cooperation in relations with the community, and (9) a conducive academic climate in the madrasah.